PAINTING AND ITS TYPES: EXPLORING TECHNIQUES, STYLES, AND ARTISTIC EXPRESSION - Baratbayev Batir Mamadjonovich (Galaxy International Interdisciplinary Research Journal, 2024)
This scientific article explores the captivating world of painting, a diverse and expressive medium that has been integral to human artistic expression for centuries. The article provides an overview of painting as an art form, delving into its historical significance, materials, techniques, and various types. It examines the distinct characteristics, styles, and artistic movements associated with different types of painting, including oil painting, watercolor, acrylic, fresco, and mixed media. The article also explores the ways in which artists utilize painting to convey emotions, narratives, and personal perspectives. By examining the types of painting and their artistic qualities, this article aims to deepen our understanding and appreciation of this timeless form of visual art.